Digital game-based learning in mathematics learning with cultural contexts: A systematic literature review - Zea Zisman Usman; Nanang Priatna; Dadang Juandi; Trisonia Fitria (Universitas Muhammadiyah Surakarta, 2026)
The increasing integration of digital technologies into education has encouraged the use of Digital Game-Based Learning (DGBL) to enhance students’ engagement and mathematical understanding; however, research on incorporating cultural contexts into DGBL for mathematics learning remains fragmented and lacks a comprehensive synthesis. This study aims to systematically review existing literature on culturally contextualized DGBL in mathematics education by identifying dominant research designs, participant characteristics, mathematical content, cultural representations, learning outcomes, and future research directions. A systematic literature review was conducted following the PRISMA framework using data retrieved from the Scopus database with the keywords